A co-evolution perspective of EMNE internationalization and institutions: An integrative framework of 5Cs. Issue 4 (August 2021) - Chidlow, Agnieszka; Wang, Jue; Liu, Xiaohui; Wei, Yingqi
Abstract: While significant progress has been made on the contextual role of institutions, scholarly research on the dynamic process of emerging economy multinational enterprises' (EMNEs) international activities interacting with home country and host country institutions still seems to be in its infancy. Therefore, in order to move the current academic debate forward, we examine the intersection between the internationalization of EMNEs and their institutional environments by undertaking a critical review of the existing literature, given that institutional forces not only shape organizational behavior but also affect EMNEs' internationalization strategies and organizational outcomes. We propose an integrative framework of 5Cs (context, capability, change, concomitance and configuration) underlying the co-evolution of EMNEs' internationalization and institutions, and position all the papers included in this Special Issue within this framework in order to point towards a number of directions for future scholarship.